Perancangan Wireframe UI/UX Aplikasi Mobile HyperCare bagi Penderita Hipertensi Menggunakan Metode Design Thinking - Sugiharto, Sigit; Wirawati, Maulidta Karunianingtyas; Aini, Dwi Nur (SENTRI: Jurnal Riset Ilmiah, 2025)
Hypertension is a chronic disease that serves as a major cause of serious complications such as stroke and heart disease. A common issue faced in managing hypertension is the lack of patient adherence to treatment and health monitoring. To address this challenge, a mobile application was developed specifically to assist hypertensive patients in monitoring their blood pressure, participating in peer group chats, and accessing health education. The app design process began with the creation of a wireframe as an initial visual representation of the app’s interface and user flow. The development method used was Design Thinking, which consists of five stages: empathize, define, ideate, prototype, and test. Through these stages, observations and interviews were conducted with hypertensive patients to explore their needs and challenges. Based on these findings, a wireframe was developed and tested with users to gather feedback. Evaluation results showed that the wireframe successfully met user needs, particularly in terms of ease of use, informative design, and features relevant to their health condition. Therefore, the Design Thinking approach proved effective in designing technology-based solutions that align with the needs of individuals living with hypertension.